Supply chain management in pharmaceutical industries: supply chain of Incepta Pharmaceuticals Limited - Naushad, Mohammad Yasir (BRAC University, 2019)
This dissertation is submitted in partial fulfillment of the requirements for the degree of Masters in Procurement and Supply Management, 2018.